2001
DOI: 10.1046/j.0953-816x.2001.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychosocial stress differentially affects apoptosis in hippocampal subregions and cortex of the adult tree shrew

Abstract: We studied the effect of chronic psychosocial stress on cell death and volume changes in the tree shrew hippocampus. In situ end labelling (ISEL) identified low frequent but convincing apoptosis in many hippocampal subregions. Also in entorhinal cortex, apoptosis was found, generally at higher frequencies. After 28 days of chronic stress, apoptosis was significantly reduced in the CA1 stratum radiatum, whereas an increase was observed in the hilus (P < 0.04). With all subregions taken together, the hippocampus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(77 citation statements)
references
References 41 publications
8
67
0
2
Order By: Relevance
“…Thus, not only cytogenesis but also cell death, and therefore the entire process of adult dentate gyrus neuronal turnover, is affected by tianeptine treatment. In line with the antiapoptotic effect observed post-mortem by Lucassen et al, 85 tianeptine prevented the stressinduced reduction of the in vivo brain metabolite levels of N-acetylaspartate. 22 Several other studies have shown protective effects of antidepressants in different models, and mostly in the hippocampus.…”
Section: Cytoprotective Effectssupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, not only cytogenesis but also cell death, and therefore the entire process of adult dentate gyrus neuronal turnover, is affected by tianeptine treatment. In line with the antiapoptotic effect observed post-mortem by Lucassen et al, 85 tianeptine prevented the stressinduced reduction of the in vivo brain metabolite levels of N-acetylaspartate. 22 Several other studies have shown protective effects of antidepressants in different models, and mostly in the hippocampus.…”
Section: Cytoprotective Effectssupporting
confidence: 75%
“…Both stress and tianeptine had region-specific effects and tianeptine treatment reduced apoptosis in the dentate granule cell layer and subgranular zone, most likely on non-neuronal cells, but had no effect in the Ammon's Horn. These effects were not restricted to the hippocampus alone, as in the temporal cortex, chronic stress alone increased the numbers of apoptotic cells, 85 while tianeptine treatment had an antiapoptotic effect both in the stressed and unchallenged animals 84 (Figure 6). …”
Section: Cytoprotective Effectsmentioning
confidence: 96%
“…Therefore, stress may perturb gene expression transiently, perhaps via epigenetic effects [97,143], but the withdrawal of the inciting stimulus leads to re-instatement of the original, fully programmed 'steady state.' In addition, whereas neuronal loss has been suspected to occur upon chronic stress in the adult [125,90], most current evidence supports the notion that the structural effects of chronic stress on hippocampal neurons involve dendritic modifications, without cell loss or profound dendritotoxicity. Thus, upon withdrawal of the molecular processes initiated by stress, recovery of both function and structure occurs in mature hippocampus [109,56,114].…”
mentioning
confidence: 52%
“…An important feature of the present stress manipulations is their episodic nature, which differs from the life-threatening effects of continuous subordination stress (Blanchard et al, 1985;Miczek et al, 1991;Von Holst, 1998;Lucassen et al, 2001;Carr, 2002).…”
Section: Discussionmentioning
confidence: 99%